The positive perception of reduced gang violence through a public safety initiative. (June 2019) - Gahunia, Shaveta; McConnell, Keiron; Bain, Andy
Gang violence poses a significant concern for the police and the public. In response, in 2008 policing agencies in British Columbia introduced Restaurant Watch, a targeted strategy aiming to deter unwanted gang-involved patrons from attending participating restaurants. In response to a lack of research, the present study examines the perceived success of the programme, through semi-structured interviews with key stakeholders participating in the programme. The findings suggest the programme has value based on three important themes: (1) impact on public safety; (2) importance of partnership and open dialogue; and (3) ability to deter inadmissible patrons from participating establishments.